Protocol for a qualitative pilot study to explore ethical issues and stakeholder trust in the use of normothermic regional perfusion in organ donation in Canada. Issue 9 (29th September 2022) - Murphy, Nicholas; Lingard, Lorelei; Blackstock, Laurie; Ott, Mary; Slessarev, Marat; Basmaji, John; Brahmania, Mayur; Healey, Andrew; Shemie, Sam; Skaro, Anton; Wilson, Lindsay; Weijer, Charles
Abstract : Introduction: The process of controlled organ donation after circulatory determination of death (cDCDD) results in ischaemic injury to organs and leads to poorer outcomes in organ recipients. Although not yet used in Canada, normothermic regional perfusion (NRP) is a perfusion technology used postmortem with cDCDD donors to selectively restore perfusion of oxygenated blood to target organs in situ, reversing ischaemic injury and improving organ viability and post-transplant outcomes. However, NRP poses significant ethical challenges. To preserve trust in deceased donation, these ethical challenges must be addressed to the satisfaction of Canadian stakeholders before NRP's implementation. This study will identify ethical issues pertaining to NRP and explore perspectives of NRP among key stakeholders. By developing an explanatory framework delineating how stakeholder perceptions of NRP's ethical implications impact trust in Canada's donation and transplantation systems, this study will inform the development of responsible policy on NRP's use in Canada. Methods and analysis: This study includes two workstreams. Workstream 1 is a scoping review of medical and bioethical literature to identify ethical issues stemming from NRP. We will apply a common search string across Medline, PubMed (other than Medline) and Embase to identify relevant articles. We will identify grey literature through Google searches, websites of organ donation organisations and consultation with our research network. No date limits will be applied. All peer-reviewed publications, commentaries, editorials or documents that engage with ethical issues in NRP (or conceptual and empirical issues as they relate to these ethical issues) will be included. News articles, conference abstracts and publications not in English will be excluded. Workstream 2 consists of interviews with healthcare providers, institutional stakeholders, organ recipients and deceased donors' family members (n=24–36), as well as focus groups with healthcare providers involved in deceased donation and transplantation (n = 20–32). Constructivist grounded theory methodology will guide data collection and analysis in workstream 2. Ethics and dissemination: This study was approved by Western University's research ethics committee (Western REM; ID: 120001). All participants will be asked to provide written informed consent to participate. Findings will be shared with Canadian organ donation and transplantation organisations, presented at national conferences and published in medical journals.